2010
DOI: 10.2174/138161210794454996
|View full text |Cite
|
Sign up to set email alerts
|

Using Insights into Pim1 Structure to Design New Anticancer Drugs

Abstract: Human Pim1 (proviral integration site for Moloney murine leukemia virus) kinase is a 313-amino acid serine-threonine kinase that possesses several biological functions in cell survival, proliferation and differentiation, and its overexpression has been observed in a number of human cancers. Indeed, this kinase is a proto-oncogene that has been implicated in early transformation and tumor progression, especially in hematopoietic malignancies and prostate carcinoma where it is a marker of a poor prognosis. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 79 publications
1
17
0
Order By: Relevance
“…When the distance threshold is set to 4.5 Å , the ATP-mimetic inhibitor BIM-1 (PDB code: 1XWS, Figure 3A), the ATPcompetitive inhibitor K00135 (PDB code: 2C3I, Figure 3B), the phenylpyrimidine analog (PDB code: 3DCV, Figure 3D), the hydroxybenzofuran derivative I (PDB code: 3UMX, Figure 4A) and the quinazoline derivative (PDB code: 3UIX, Figure 4C) interact with various residues, including Leu44, Gly45, Phe49, Val52, Ala65, Lys67, Ile104, Leu120, Glu121, Arg122, Val126, Asp128, Glu171, Leu174, Ile185 and Asp186, as summarized in Table 3. Schenone et al [57] also reported that more than 60% of 25 inhibitors analyzed interacted with Leu44, Val52, Ala65, Ile104, Leu120, Leu174 and Ile185.…”
Section: 4mentioning
confidence: 94%
See 1 more Smart Citation
“…When the distance threshold is set to 4.5 Å , the ATP-mimetic inhibitor BIM-1 (PDB code: 1XWS, Figure 3A), the ATPcompetitive inhibitor K00135 (PDB code: 2C3I, Figure 3B), the phenylpyrimidine analog (PDB code: 3DCV, Figure 3D), the hydroxybenzofuran derivative I (PDB code: 3UMX, Figure 4A) and the quinazoline derivative (PDB code: 3UIX, Figure 4C) interact with various residues, including Leu44, Gly45, Phe49, Val52, Ala65, Lys67, Ile104, Leu120, Glu121, Arg122, Val126, Asp128, Glu171, Leu174, Ile185 and Asp186, as summarized in Table 3. Schenone et al [57] also reported that more than 60% of 25 inhibitors analyzed interacted with Leu44, Val52, Ala65, Ile104, Leu120, Leu174 and Ile185.…”
Section: 4mentioning
confidence: 94%
“…X-ray structural analyses revealed the presence of an extensive network of a salt bridge (Arg166--Asp200) and hydrophobic interactions (Leu164, Leu193, Tyr198 and Phe201) between the A-loop and the C-loop, and the hydrogen bonds (Leu192-Tyr198, Lys194-Val197) inside the A-loop are crucial for opening the ATP binding pocket and stabilizing the active conformation [52]. The structures of the ATP binding pockets in protein kinases are quite similar, and thus the development of a highly selective drug is difficult [55][56][57]. Protein kinases commonly form two hydrogen bonds with the ATP adenine through the residues in the hinge region, while Pim1 forms only one hydrogen bond, between the N6 atom of the ATP adenine ring and the backbone carbonyl oxygen atom of the first hinge residue (Glu121) ( Figure 2B) [50][51][52].…”
Section: Structural Features Of Pim1mentioning
confidence: 99%
“…They are particularly active on the proviral integration site for Moloney murine leukemia virus (PIM) kinases, which are involved in the development of different tumors [67]. However, some derivatives demonstrate a good activity on Bcr-Abl T315I, and in particular compounds 31a --c ( Figure 10) show IC 50 values of 0.07, 0.03 and 0.07 mM, respectively.…”
Section: Patents Published In 2012mentioning
confidence: 99%
“…5,9 Pim family consists of structurally homologous members with Pim-1 and Pim-2 sharing 61% similarity while Pim-1 and Pim-3 having 71% similarity at the amino acid level. 2 This offers a unique opportunity to generate highly specific small molecule inhibitors against all three pim kinases.…”
Section: 8mentioning
confidence: 99%